RELASI KEKUASAAN DAN PENGETAHUAN PADA ARSITEKTUR GEREJA CANDI GANJURAN - Prisca Bicawasti Budi Sutanty (Nature : National Academic Journal of Architecture, 2023)
Other than technique function and building aesthetic, architecture represents power relation and knowledge in its design. The architect’s knowledge will crystallize into a building as a text, and visitors can read it. This research discusses the relation between power and knowledge, which produces discourse in the design of Ganjuran Temple Church, Yogyakarta. The method that was used is qualitative descriptive and random probability sampling. This research reveals the relationship between power and knowledge owned by architects and explains the discourse. Architect’s ideology is about expanding the gospel wrapped by Mataram culture. The message is delivered in 6 concepts consisting of 13 architectural elements. The mean value results show that visitors know there are messages behind the building, but they do not understand the majority meaning. As locals see the common form, Mataram culture dominates the knowledge. So Mataram culture is the strongest discourse from visitors’ view. On the contrary, as the newest ideology for Javanese society, the Catholic value is the lowest readability because of the implementation of minor elements that is not the visitors’ focus.